LITERATURE REVIEW: ANALISIS DAMPAK LIMBAH RUMAH TANGGA TERHADAP LINGKUNGAN DI DESA STUNGKIT KECAMATAN WAMPU - Nur Muthmainah; Rizki W Chaniago; Siti Khadijah Purba; Abdurrozzaq Hasibuan (Cross-border, 2023)
Garbage is still an environmental problem in various parts of the world, including Indonesia. Garbage can come from households, which are always produced every day. Household waste, namely waste originating from bathrooms, kitchens, washing water, used household waste, and human waste. The purpose of this research is to explain the effect of household waste on environmental health and how to handle it. This research shows that there are many negative impacts caused by household waste. Waste that is not managed properly will have a negative impact on the environment so that the environment becomes polluted.